Outer membrane protein analysis of ampicillin-resistant isolates of Haemophilus influenzae from Saudi Arabia - Ronald A. Dixon; Eyad M. Abdel-Rahman (Elsevier, 2008)
Summary: Haemophilus influenzae isolates characterized in a previously published study from the Kingdom of Saudi Arabia were analysed by outer membrane protein (OMP) profiling. Isolates from patients with confirmed respiratory tract infections were investigated. Antibiotic susceptibility tests in vitro showed 25/129 (19.4%) had various degrees of reduced susceptibility to ampicillin although all were fully susceptible to ceftazidime and ciprofloxacin. OMP profiles of the β-lactamase mediated ampicillin-resistant and β-lactamase negative; ampicillin intermediate resistant strains (BLNAI) isolated were investigated. Dendrograms of scanned SDS-PAGE of these strains showed 15 different groupings from the 15 non-typable (NTHi) isolates tested demonstrating a high degree of heterogeneity whereas the 5 Hib isolates demonstrated significantly closer relatedness and were probably clonal. The present study demonstrates the groupings of H. influenzae strains by OMP profile analysis which did not correlate with the β-lactamase production ability, BLNAI isolates, geographical origin or biotype. Keywords: Haemophilus influenzae, Antibiotic resistance, Outer membrane proteins, Saudi Arabia